TREATMENT TACTICS FOR ANORECTAL ANOMALIES IN GIRLS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This study describes the surgical treatment of 114 girls born with anorectal anomalies , taking into account the anatomical form of the anomaly , its development, and concomitant anomalies. The advantages of a single-stage surgical treatment and indications for a multi-stage surgical treatment with colostomy are based on the results.
Keywords: Anorectal defects, girls, method of treatment.